Konflik Kerja Keluarga Dengan Kepuasan Kerja Yang Dimoderasi Komitmen Organisasi Pada Karyawan Bali - Ni Made Adelia Surya Anjani; Nicholas Simarmata (Jurnal Psikologi Udayana, 2017)
Many demands of role that already undertaken by Balinese people who work as employees, makes the employees work under pressure and confuse facing the responsibility on each role. This situation can lead them to work family conflict. A form of interrole conflict in which the role pressures from the work and family domains are mutually incompatible in some respect (Greenhaus & Beutell, 1985). The conflict will push the work conflict, which has the potential to reduce the level of job satisfaction. However, the relationship between work family conflict with job satisfaction can be stronger when it involves the organizational commitment in both cases. Therefore, this study aims to see the relationship between work family conflict with job satisfaction, and examine the relationship between work family conflict on job satisfaction and organizational commitment as moderator. This is a correlation quantitative method. Respondents involves this study are 150 Balinese employees who have family, minimum at high school degree, have been working for 1 year in their company, minimum age 20 years, and has status as a permanent employee. Reliability scores for work family conflict scale is 0,876, reliability scores for job satisfaction scale is 0,864, and reliability scores for organizational commitment is 0,924. Data distribution has shown normal and linear distribution. The result of moderator variable regression analysis by sub-group method shows that organizational commitment doesn’t moderate the effects of work family conflict to job satisfaction on Balinese employees (F count value (1,066) < F table value (3,10)). Keywords: Work Family Conflict, Job Satisfaction, Organizational Commitment, Balinese Employees